The Effect of Self-Financing on Learning Motivation with Mediation of Training Quality - Setyowati, Endang; Sawitri, Dyah (MEC-J (Management and Economics Journal), 2021)
This study aims to examine the effect of Self-financing on Training quality and the impact on learning motivation of trainees at UPT BLK Singosari-Malang. This research is important because in the researchers knowledge it has never been studied before and can contribute to Singosari BLK UPT to determine appropriate Self-financing and training. The study population was 60 participants who had attended training at UPT BLK Singosari during 2019 using Self-financing. Because the samples are small, this study uses a census sample, where a total of 60 people are sampled. Data collection uses a questionnaire. Data was obtained by distributing a list of questions about the Self-financing variable and Training quality in relation to learning motivation to respondents. The data obtained were analyzed by multiple regression analysis and path analysis. The results showed that Self-financing directly has a significant effect on Training quality variable. Self-financing directly has a significant effect on variable Learning motivation. The Training quality directly has a significant effect on Learning motivation variable. Self-financing indirectly has a significant effect on Learning motivation mediated by Training quality.